Some Selected Properties of Two MalaysianBamboo Species in Relation to Age, Height, Site and Seasonal Variations - Mohmod, Abd. Latif (1996)
Bamboo is widely found in Peninsular Malaysia but little research has been conducted on its importance and suitability for industrial use. A study was initiated to determine the variation and correlations of anatomical, chemical, physical, mechanical and machining properties of two bamboo species, namely Bambusa vulgaris schrad 'Buluh minyak' and Gigantochloa scortechinii Gamble 'Buluh semantan' in relation to age, height, site and season. The anatomical properties differed significantly with species, are generally stable with site, had no significant relationship with age from one to four years old and decreased with culm height. B. vulgaris fibres (1.9 - 2.4 mm) were shorter than those of G. scortechinii (2.7 - 5.6 mm). The average fibre sheath percentage and cell wall thickness of both bamboo species ranged from 32 to 49 % and 2 to 13 µm, respectively. Based on the Runkle ratio, older culms of both bamboo species appeared to be potential pulping materials. The anatomical structures correlated positively with density, mechanical properties, recovery rate and product quality but are inversely correlated with moisture content and dimensional shrinkages.